Prarancangan Pabrik Metanol Proses Lurgi-Low Pressure Methanol Dengan Disain Alat Utama Destilasi Metanol - Reno Susanto; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Domestic demand for methanol continues to increase, it was recorded that in 2018 Indonesia imported 701,291.5 tons of methanol, which was the highest import compared to previous years. Methanol is widely used globally for industrial applications including acetic acid, formaldehyde, MTBE, polyvinyl, polyester and DME industries. The main raw material used in the manufacture of methanol with the Low Lurgi Pressure process is natural gas. This factory is planned to operate for 330 days per year and work continuously for 24 hours / day with a capacity of 200,000 tons / year which will be established in the Pelintung Industrial area, Dumai, Riau. The remaining time during the operation process is used for shutdown, plant maintenance, maintenance and repair of equipment. The design of the main equipment in this plant is the Methanol Distillation which functions to separate methanol from water. The distillation tower is operated at a pressure of 1 Bar and a temperature of 95 ° C. The economic analysis in this plant design shows that the methanol plant with the lurgi-low pressure methanol process with the main methanol distillation tool design is feasible to be established with a BEP value of 41% and a Payback Period (PBP). ) 3,008 years factory. Keywords: Methanol, Economic Analysis, Natural Gas,